Impact of zinc oxide nanoparticles and ocean acidification on antioxidant responses of Mytilus coruscus - Huang, Xizhi; Liu, Yimeng; Liu, Zekang; Zhao, Zihao; Dupont, Sam; Wu, Fangli; Huang, Wei; Chen, Jianfang; Hu, Menghong; Lu, Weiqun; Wang, Youji (Chemosphere (Oxford), 2018)
Increased production of engineered nanoparticles (NPs) has raised extensive concerns about the potential toxic effects on marine organisms. Extensive evidences documented the impact of ocean acidification (OA) on the physiology and fitness of bivalves. In the present study, we investigated the biochemical responses of the mussel Mytilus coruscus exposed to both nano-ZnO and low pH relevant for ocean acidification conditions for 14 d followed by a 7-d recovery period. Most biochemical indexes (superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), acid phosphatase (ACP) and alkaline phosphatase (ALP)) measured in gills and hemocytes were increased when the mussels were subject to low pH or high concentration of nano-ZnO, suggesting oxidative stress responses. No significant interactions between the two stressors were observed for most measured parameters. After a 1 week recovery period, low pH and nano-ZnO had less marked impact for SOD, GPx, ACP and ALP in hemocytes as compared to the end of the 14 d exposure. However, no recovery was observed in gills. Overall, our results suggest that both low pH and nano-ZnO induce an anti-oxidative response in Mytilus coruscus with gills being more sensitive than hemocytes. [Display omitted] •Combined effects of pH and nano-ZnO on biochemical responses of mussels are investigated.•Low pH and nano-ZnO induce a similar anti-oxidative responses.•Gills are not only susceptible to nano-ZnO but also seawater acidification.